2015
DOI: 10.3748/wjg.v21.i13.3994
|View full text |Cite
|
Sign up to set email alerts
|

Importance of reporting segmental bowel preparation scores during colonoscopy in clinical practice

Abstract: Segmental AADRs correlate with segmental BBPS. It is thus valuable to report segmental BBPS in colonoscopy reports in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…In combination with Clarks' study, this current study also helps inform clinicians with respect to anticipated risks for future polyps based on initial BBPS segment scores, which may guide shared decision making with patients. Past studies estimated risks of missed polyps due to inadequate bowel cleanliness based on colonoscopy examinations at a single time point, comparing polyp detection across different categories of bowel cleanliness, 19,25,26 rather than evaluating interval findings on repeat colonoscopy as our current study did.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with Clarks' study, this current study also helps inform clinicians with respect to anticipated risks for future polyps based on initial BBPS segment scores, which may guide shared decision making with patients. Past studies estimated risks of missed polyps due to inadequate bowel cleanliness based on colonoscopy examinations at a single time point, comparing polyp detection across different categories of bowel cleanliness, 19,25,26 rather than evaluating interval findings on repeat colonoscopy as our current study did.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that when there is good bowel preparation with higher overall BBPS score, the ADR and AADR are higher. Jain D et al [22] indicated that AADR for bowel preparation with BBPS 7–9 was 16.7%, for BBPS = 4–6 was 14.8% and for BBPS = 0–3 was only 3.8%. There was statistically significant difference for the 3 groups ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This simple fact is underlined by multiple studies and guidelines [36,37,38]. A good bowel preparation is identified as a quality marker for colonoscopy [10].…”
Section: Factors Influencing the Adrmentioning
confidence: 99%